360 tour / Nur Alya Ahmad Azmi - Ahmad Azmi, Ahmad Azmi (Universiti Teknologi MARA, Kedah, 2014)
Design Show 2014 is meant to provide a fundamental platform for all the students, especially those in the final year, to exhibit and showcase their talent and skills. This platform is essential and it works as the basic ground for the students to explore more in their professional worlds in the future. It is also meant to provide a medium to explore new, innovative and enterprising ideas and as well as to present a common platform for the potential clients and employers in searching the new talents.